Breast Lipomodelling Outcome Following Conservative Breast Cancer Surgery and Reconstructive Surgery in a District Hospital - M. Metry; M. Shaaban; B. Edgar; M. Youssef; N. Mclean; M. Carr; P. Sierra (New Frontiers in Medicine and Medical Research Vol. 9, 2021)
Lipomodelling has been increasingly used recently for the correction of defects and asymmetry following oncologic breast cancer treatment [1]. Current evidence on the efficacy of breast reconstruction using lipomodelling after breast cancer treatment is inadequate and the evidence raises no major safety concerns [2]. We have audited our outcome results against the NICE guidelines criteria for both safety and efficacy. Data was collected retrospectively of all the lipomodelling cases performed in Northumbria Healthcare NHS Foundation Trust between 04/2011-04/2013. A total of 36 patients were included in the study, the average amount of fat injected was 113.91mls per session, Cytori technique gave the least complications rate 11% vs Coleman and body jet techniques 44% and 45% respectively. We met the NICE guidelines criteria in; number of sessions for each patient, the duration of hospital stay and we documented the amount of fat harvested and injected in each patient. We didn’t fulfil the guidelines in: volume change; as no definite tool was used other than clinical assessment; 80% were very good and good aesthetic outcome compared to NICE’s 87%, while aesthetic outcome was absent in 8% compared to NICE’s 2.7%. Regarding the safety, we met the NICE’s guidelines in local recurrence rates <1%, and local infection rate<1%, as well as pneumothorax and fat embolism (0%). However; we had a high liponecrosis rate 13% vs 3%, and liponecrotic cysts (8.33% vs 7%), these were more frequent with Body jet technique. Conclusion: Lipomodellingis a safe procedure following breast cancer surgery which can be carried out at District general hospitals levels with comparable outcomes.